Changes in Soil Physico-Chemical and Microbiological Properties During Natural Succession: A Case Study in Lower Subtropical China - Zhao, Xinyu; Liu, Peiling; Feng, Yingjie; Zhang, Weiqiang; Njoroge, Brian; Long, Fengling; Zhou, Qing; Qu, Chao; Gan, Xianhua; Liu, Xiaodong (Frontiers in Plant Science, 2022)
Vegetation succession can change the function and quality of the soil. Exploring the changes in soil properties during secondary forest restoration is of great significance to promote forest restoration and improve the ecological service function of subtropical ecosystems in South China. In this study, we chose three typical forests in subtropical China as restoration sequences, broadleaf-conifer mixed forest (EF), broadleaved forest (MF), and old-growth forest (LF), to study the changes in soil physico-chemical and biological properties and the changes of soil comprehensive quality during the secondary succession of subtropical forest. The results showed that the soil physical structure was optimized with the progress of forest succession. The soil bulk density decreased gradually with the progress of forest restoration, which was significantly affected by soil organic carbon (P<0.01). In LF, the soil moisture increased significantly (P<0.05), and its value can reach 47.85±1.93%, which is consistent with the change of soil porosity. With the recovery process, soil nutrients gradually accumulated. Except for total phosphorus (TP), there was obvious surface enrichment of soil nutrients. Soil organic carbon (15.43±2.28 g/kg), total nitrogen (1.08±0.12 g/kg), and total phosphorus (0.43±0.03 g/kg) in LF were significantly higher than those in EF (P<0.05). The soil available nutrients i.e., soil available phosphorus and available potassium decreased significantly in LF (P<0.05). In LF, more canopy interception weakened the P limitation caused by atmospheric acid deposition, so that the soil C:P (72.33±6.90) and N:P (4.64±0.35) in LF were significantly lower than those in EF (P<0.05). Affected by TP and moisture, microbial biomass C and microbial biomass N increased significantly in LF, and the mean values were 830.34±30.34 mg/kg and 46.60±2.27 mg/kg, respectively. Further analysis showed that total soil porosity (TSP) and TP (weighted value of 0.61) contributed the most to the final soil quality index (SQI). With the forest restoration, the SQI gradually increased, especially in LF the value of SQI was up to 0.84, which was significantly higher than that in EF and MF (P<0.05). This result is of great significance to understanding the porcess of restoration of subtropical forests and improving the management scheme of subtropical secondary forests.